2007
DOI: 10.1097/sla.0b013e31813e8a56
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Outcome After Gastric Banding

Abstract: This nationwide survey shows that the best profile for a success after gastric banding is a patient <40 years, with an initial BMI <50 kg/m, willing to change his eating habits and to recover or increase his physical activity after surgery and who has been operated by a team usually performing >2 bariatric procedures per week. This study emphasizes that obesity surgery requires a significant experience of the surgical team and a multidisciplinary approach to improve behavioral changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…Self-reported adherence to the post-operative dietary guidelines predicted greater weight loss [49] [52]. Similarly, failure to change eating habits increased the risk two-fold of losing <50 EWL% two years post-operatively [8]. Lower dietary intake, calculated from patient food diaries at 8 years after surgery, was associated with >50 EWL% [53].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-reported adherence to the post-operative dietary guidelines predicted greater weight loss [49] [52]. Similarly, failure to change eating habits increased the risk two-fold of losing <50 EWL% two years post-operatively [8]. Lower dietary intake, calculated from patient food diaries at 8 years after surgery, was associated with >50 EWL% [53].…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen additional studies were identified in the current review that examined post-operative exercise and weight loss outcomes [5, 8, 31, 33, 36-38, 50-53, 56-63], and all but three [31, 53, 58] found that patient-reported post-surgery exercise frequency was significantly associated with weight loss outcome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The weight reduction is clinically significant when followed by the resolution of, or improvement in, comorbidities and when it is accompanied by a significant reduction in predicted risk of major complications [5,31]. It is possible that studies that identified excess weight loss of <50 % were not able to detect a significant improvement in comorbidities; in these cases, the reduction in BMI was not sufficient to have an impact on drug use and drug costs.…”
Section: Discussionmentioning
confidence: 98%
“…BS has been able to reverse or improve comorbidities associated with obesity, such as hypertension, diabetes mellitus (DM), and dyslipidemia. Surgical treatment is considered successful when over 50 % of the patient's excess weight has been lost and the weight loss maintained at least 5 years after the procedure, but success is often determined by the patient's perceived improvement in quality of life [5,6]. The surgical procedure is not free of risks and requires long-term nutritional and pharmacologic monitoring [7].…”
Section: Introductionmentioning
confidence: 99%